“Whose Fault Is It?” How Rural Chinese Women Explain Intimate Partner Violence: A Qualitative Study - Hou, Fengsu; Cerulli, Catherine; Wittink, Marsha N.; Caine, Eric D.; Qiu, Peiyuan (Frontiers in Psychiatry, 2021)
Women are often the victims of intimate partner violence (IPV). Though China has established its first statute against domestic violence, the service developments for victims fall behind. It is important to assess community members' perceptions of what causes IPV to create interventions to prevent and address IPV. This study completed the Short Explanatory Model Interview (SEMI) among a subset sample from a large epidemiology study in rural Sichuan China. The social ecological model was applied to analyze qualitative interviews. Among 339 participants, the average age was 46.01 ± 12.42 years old. There were 31.86% of them had been educated, 14.75% of them had migrant worker partners, and 49.26% of them had experienced violence from their partners in the last year. There were 252 participants attributed IPV to individual factors, and they primarily discussed the social characteristics, behaviors, personalities or even health problems of the husband or the wife in the vignette. Under this theme, there were 86 participants blaming the victim for being anxious, social disconnectedness or lazy; and there were 166 participants blaming to the perpetrator being abusive, irresponsibility, lack of understanding, and cheating. There were 44 women believed the cause was relational, in which there were 41 participants attributed the problem to the broken relationship between the couple and three participants attributed to the lack of support. There were 28 participants believed the cause was communal and societal, such as being poor, family problems, fate, and believed IPV was a common scene. There were 15 participants could not identify the cause of IPV. These participants usually provided very brief responses and barely had insight on violent behaviors or confidence in discussing the cause. Our findings offer a direction for understanding the rural Chinese women's beliefs about the etiology of IPV to better develop interventions which must consider raising a public awareness campaign about the risk factors of IPV and focus on reducing self-blame among victims.